Who Bears the Burden of Environmental Policies within Countries? - Estache, Antonio; Savard, Luc (World Bank, Washington, DC, 2012)
This report summarize on the burden of environmental policies within countries. Climate change policies will have distributional consequences across and within countries. Most of the current environmental policy instruments tend to be regressive and impose a higher burden on the poor. Despite their limitations, more systematic incidence assessments for climate change (CC) policies are needed so that adaptation and mitigation policies address their distributional effects within countries.